THE EFFICIENCY OF WORKING CYCLES IN THE RAPID INTERNAL COMBUSTION ENGINE WITH THE EXTENDED WORKING STROKE - Hashchuk P. М.; Nikipchuk, S. V. (Science and Transport Progress, 2020)
Purpose: The investigation covers the efficiency of working cycles in the rapid internal combustion engine with the extended working stroke. The extended working stroke is applied in so-called Atkinson/Miller engines that are considered to be more effective than traditional Otto engines. Methodology. In order to identify purely distinctive features of different working cycles, they were investigated in an idealized form using the concepts of a conditional working cycle, quantitative as well as qualitative characteristics of the working fluid. Findings. The investigation illustrates the following: 1) the Otto engine should have a significantly larger displacement to function the same way as the Atkinson/Muller engine; 2) if the mechanic work is predetermined, the efficiency coefficient and the course of expansion of the Atkinson-Miller cycle increase until it turns into the Humphrey cycle; 3) the increase of Otto engine’s efficiency using Attkinson’s means involves larger displacement if the engine was efficient from the very beginning. Originality. Attkinson’s engine may significantly lose its efficiency in energy at partial loads. If in the process of virtual design of the Atkinson engine the energy-saving advantages of Humphrey cycle become noticeable, then in the process of imaginary regulation of the thrust of an already synthesized engine of this type the advantages of this cycle are no longer traceable. Practical value. In general, the Otto engine could be considered as a still profitable technical compromise between a two-stroke engine and the Atkinson engine. On the one hand, increasing the efficiency coefficient of a rapid internal combustion engine contributes to significant fuel savings and environmental hazards reduction throughout the life cycle of a machine driven by such an energy-saving engine. But on the other hand, the implementation of the energy-saving Atkinson/Miller working cycle will be accompanied by an increase in the mass and size of the engine and will negatively affect the properties of the machine.